Self-Organization for collective action: An experimental study of voting on formal, informal, and no sanction regimes - Thomas Markussen; Louis Putterman; Jean-Robert Tyran (Brown University, Department of Economics, 2011)
Entrusting the power to punish to a central authority is a hallmark of civilization. We study a collective action dilemma in which self-interest should produce a sub-optimal outcome absent sanctions for non-cooperation. We then test experimentally whether subjects make the theoretically optimal choice of a formal sanction scheme that costs less than the surplus it makes possible, or instead opt for the use of informal sanctions or no sanctions. Most groups adopt formal sanctions when they are of deterrent magnitude and cost a small fraction (10%) of the potential surplus. Contrary to the standard theoretical prediction, however, most groups choose informal sanctions when formal sanctions are more costly (40% of the surplus). Being adopted by voting appears to enhance the efficiency of both informal sanctions and non-deterrent formal sanctions.
Keywords: C92; C91; D03; D71; H41; 330; formal sanctions; informal sanctions; experiment; voting; cooperation; punishment